2014
DOI: 10.3133/ofr20141114
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of suspended-sediment transport, bedload, and dissolved oxygen during a short-term drawdown of Fall Creek Lake, Oregon, winter 2012-13

Abstract: rapid fouling of the probe by the large amount of sediment in transport. Dissolved oxygen returned to background levels downstream of Fall Creek Dam on December 18, 2012, approximately 1 day after the end of the drawdown operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Where transport capacity is low relative to sediment supply, the deposition can be persistent. For example, in some low-velocity, off-channel areas of Fall Creek and Middle Fork Willamette River, fine sediments released from annual drawdowns at Fall Creek Reservoir have deposited and remained stable despite multiple high-flow events (Schenk and Bragg, 2014;Bangs and others, 2015;16;Keith and others, 2017). Evaluating current patterns of bedmaterial texture and monitoring future changes are critical for determining whether environmental flow releases could be implemented to minimize negative effects such as armoring in main channel habitats and excessive fine sediment aggradation in off-channel habitats.…”
Section: Approaches For Monitoring Bed-materials Texturementioning
confidence: 99%
“…Where transport capacity is low relative to sediment supply, the deposition can be persistent. For example, in some low-velocity, off-channel areas of Fall Creek and Middle Fork Willamette River, fine sediments released from annual drawdowns at Fall Creek Reservoir have deposited and remained stable despite multiple high-flow events (Schenk and Bragg, 2014;Bangs and others, 2015;16;Keith and others, 2017). Evaluating current patterns of bedmaterial texture and monitoring future changes are critical for determining whether environmental flow releases could be implemented to minimize negative effects such as armoring in main channel habitats and excessive fine sediment aggradation in off-channel habitats.…”
Section: Approaches For Monitoring Bed-materials Texturementioning
confidence: 99%
“…These averaged unit values were paired with either the individual samples or the averaged A and B sets (where applicable) to generate the calibration dataset. Methods for model selection follow those in Rasmussen and others (2009) and Schenk and Bragg (2014). Simple linear regressions (SLRs) and multiple linear regressions (MLRs) were evaluated to compute SSC, and log 10 transformation was applied to variables where appropriate to make model residuals more symmetric, linear, and homoscedastic.…”
Section: Surrogate Regression Methodsmentioning
confidence: 99%
“…However, turbidity is largely affected by particle density, size distribution, and composition, and experience has shown that it can be an excellent surrogate for suspended sediment, among other parameters (Lewis, 1996;others, 2008, 2009). Turbidity as a surrogate has been used to calculate suspended-sediment concentration (SSC) in the Wilson and Trask River Basins in northwestern Oregon (Sobieszczyk and others, 2015), in the Santiam River Basin (Bragg and others, 2007), in the Middle Fork Willamette River Basin (Schenk and Bragg, 2014), and in the McKenzie River (Anderson, 2007). Similar to the use of in-place turbidity measurement as a surrogate for SSC, acoustic backscatter data collected as ancillary data for the calculation of streamflow from acoustic Doppler velocity meters (ADVMs) also have been shown to be a useful surrogate for suspended sediment and P in some systems (Medalie and others, 2014).…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…By fully opening a dam outlet (e.g., gate valve), removing a physical barrier and temporarily converting the lentic reservoir into a lotic river, draining to streambed could improve the ability of juvenile salmon to locate the reservoir outlet and to pass downstream with minimal obstruction, high survival and without handling. This is effectively reservoir flushing, and may be accompanied by a washout of sediments (Schenk & Bragg, ) as well as other fish species. Although there is some history of draining for passage and dam maintenance (Anderson, ), this strategy has not previously been evaluated for short‐ and longer‐term impacts to the reservoir community.…”
Section: Introductionmentioning
confidence: 99%